Dissemination of Seagrass Density Information from Object-Based Image Analysis (OBIA) Mapping to Pengudang Coastal Community - Esty Kurniawati; Indah Kartika; Try Febrianto; Septia Refly; Mario Putra Suhana; Asep Ma’mun; Muhammad Fajar Fajri Fardillah; Muhammad Johar Rudin (Jurnal IPTEK Bagi Masyarakat, 2026)
Pengudang Village, Bintan Regency, Riau Islands, is a coastal area that hosts seagrass ecosystems with high biodiversity. However, this area is increasingly experiencing degradation pressures due to climate change and anthropogenic activities. The limited public knowledge regarding the condition of seagrass ecosystems has become a major obstacle to community-based conservation efforts in the region. This community service activity aimed to disseminate information on seagrass density mapping results using the Object-Based Image Analysis (OBIA) technology to the coastal community of Pengudang. The mapping was conducted at 59 survey points distributed across the shallow waters of Pengudang Village in October 2025. The results identified seven seagrass species with a total coverage area of 344.26 hectares, of which approximately 92% fell into the high-density category. The dissemination of the mapping results was carried out in December 2025 using an interactive outreach method supported by visual media and infographics, and was evaluated through questionnaires distributed to 10 respondents. The evaluation results showed that all assessment indicators were within a score range of 3.7–4.0, categorized as Very Good, with no respondents expressing disagreement regarding either the material or the implementation of the activity. This activity demonstrates that a dissemination approach based on modern mapping technology, delivered through participatory and contextual methods, is effective in improving public understanding, awareness, and conservation motivation among coastal communities toward seagrass ecosystems.